2012
DOI: 10.1128/aem.01602-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Linkage of Soil Carbon Pools and Microbial Functions in Subtropical Freshwater Wetlands in Response to Experimental Warming

Abstract: dRising climate temperatures in the future are predicted to accelerate the microbial decomposition of soil organic matter. A field microcosm experiment was carried out to examine the impact of soil warming in freshwater wetlands on different organic carbon (C) pools and associated microbial functional responses. GeoChip 4.0, a functional gene microarray, was used to determine microbial gene diversity and functional potential for C degradation. Experimental warming significantly increased soil pore water dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…Hyvonen et al (2007) reported that elevated N deposition may lead to a decrease in the mineralization rate and accumulation of C. SOC is a complex mixture of dissolved organic C (DOC), LOC, and ROC. DOC and LOC are direct reservoirs of readily available substrate and important for ecosystem functioning as substrates for CO 2 production (Goldberg et al, 2008;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hyvonen et al (2007) reported that elevated N deposition may lead to a decrease in the mineralization rate and accumulation of C. SOC is a complex mixture of dissolved organic C (DOC), LOC, and ROC. DOC and LOC are direct reservoirs of readily available substrate and important for ecosystem functioning as substrates for CO 2 production (Goldberg et al, 2008;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compost is also a kind of high quality organic fertilizer which can replenish various nutrients, increase microbial biomass and improve soil physicochemical properties (Clemente et al, 2012;Mackie et al, 2015;Schulz et al, 2013;Huang et al, 2008). Biochar, a solid residue from biomass pyrolysis under low oxygen conditions, has also gained increasing literature mainly because of polyaromatic and microporous structures, the large specific surface area, various surface functional groups and high cation exchange capacity (Keiluweit et al, 2010;Wang et al, 2012Wang et al, , 2013aXu et al, 2014;Liang et al, 2015a;Tang et al, 2014a). These characteristics make biochar sorb heavy metals easily and thus reduce soil ecotoxicity Tang et al, 2012;Yang et al, 2015;Wang et al, 2015bWang et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The critical roles of cellulase and ligninase in mediating SOM decomposition suggest that climate warming may affect SR through its effects on EEAs, yet we still lack direct evidence. Cellulase and ligninase are synthesized by specific groups of microorganisms (Burns et al, 2013;Carreiro et al, 2000;Wang et al, 2012), and it may take years for microbial communities to adapt to environmental changes . Thus, responses of cellulase and ligninase activities to warming may vary over time.…”
mentioning
confidence: 99%